Moderasi Reputasi Kantor Akuntan Publik pada Hubungan antara Financial Distress dan Komite Audit dengan Audit Delay - Erwin Indriyanto (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to analyze the effect of the reputation of the Public Accounting Firm (KAP) as a moderating variable in the relationship between financial distress and audit committees on audit delay in mining sector companies listed on the Indonesia Stock Exchange during the period 2017 to 2021. The methodology used in this study is a quantitative approach with a descriptive and analytical research design. The study population includes companies in the mining sector listed on the Indonesia Stock Exchange, with samples taken using the purposive sampling method. The sample selection criteria include companies that consistently publish complete annual reports and have relevant data during the study period. The data used are secondary data obtained from the company's financial statements. The variables studied include financial distress as measured by the Debt to Asset Ratio (DAR), the audit committee as measured by the number of audit committee members, and the reputation of the KAP as measured by a dummy variable based on partnership status with the Big Four KAP. Data analysis was carried out using multiple regression with the help of the Eviews statistical application. The results of the study indicate that the reputation of the KAP plays a significant role as a moderating variable in the relationship between financial distress and audit delay, but not on the audit committee and audit delay. Financial distress and the audit committee directly affect audit delay. Public interest statements Based on the results of the study, it is recommended that companies in the mining sector pay attention to the reputation of the KAP in choosing an auditor to increase stakeholder trust and reduce audit delay.